Strategi Penerapan Digital Marketing, Visual Branding, dan Operasional Manajemen untuk Meningkatkan Penjualan UMKM Keripik Cinta Rasa Desa Rowoganjar, Kabupaten Semarang - Taufiq Izzuddin; Aulia Patra Sari; Berthy Andreas Boy; Lutfi Khaidatul Ariyanti; Marshanda Liani; Septiana Putri Arafi; Vina Azharya (STIE Pelita Nusantara, 2026)
The development of Micro, Small, and Medium Enterprises (MSMEs) in the digital era faces major challenges, including limited utilization of digital-based marketing, weak visual branding, and unstructured operational management. This Community Empowerment Practical Program (KPPM) aimed to enhance the competitiveness and sustainability of Cinta Rasa Chips MSME located in Rowoganjar Village, Semarang Regency, through the implementation of digital marketing strategies, strengthening visual branding, and improving operational management. The program employed a mentoring-based community empowerment approach consisting of problem observation and identification, program planning, training and assistance implementation, evaluation, and sustainability follow-up. The activities included digital marketing training through social media and online marketplaces, redesign of product packaging and brand identity, development of standard operating procedures (SOP) for production, as well as the application of simple financial recording and inventory management systems. The results indicate an increase in product visibility through digital platforms, improvement in packaging quality and attractiveness, and enhanced partner understanding of more efficient and structured business management. The implementation of SOPs and financial recording also contributed to improved operational efficiency and better control of production costs. These findings demonstrate that the integration of digital marketing, visual branding, and operational management serves as an effective strategy to increase sales performance and strengthen the competitiveness of local potential-based MSMEs. Keywords: MSMEs, digital marketing, visual branding, operational management, community empowerment